گوجرانوالہ میں خواتین پر تشدد کے خاندانی و معاشرتی اسباب واثرات: اسلامی تعلیمات کی روشنی میں تجزیہ: Family and Social Causes and Impact of Violence on women in Gujranwala: An Analytical Study in the light of Islamic Teachings - Uzma Aslam; Dr. Ali asghar chaisti (MEI, 2023)
This article aims to highlight enactment in Pakistan regarding violence against women in the light of Islam. It is a burning issue of modern world which is trying to handle by different countries through enactment according to their customs and regional needs. Violence refers to inflicting physical and mental distress on a spirit that has a profound effect on its physical and mental organs. There are many types of violence like sexual, work place, educational and domestic etc.Sexual harassment means attempting to have any sexual or sexual orientation or the purpose of any action that is taken against a person by using intimidation or coercion by another person in a sexual relationship. The target is to have relationships anywhere in them. Gujranwala ranks fifth among the major industrial cities of Pakistan. It is as big a city as the Gujjars. The honour of women is as low as it is here today and women are treated worse by family traditions.They are not safe in their own homes nor are outside. The same stereotypes are practiced by women and women. It is targeted that the destitute woman, whether inside or outside the home, is destitute in every situation. This research describes the family and social causes of violence against women in which the family members are forced into their lives. Rights are deprived of how animals are treated when living in their own home. Violence is violent, so the rest of the family accepts the influence of the child and the community as well. Islam gives women the same rights as men and also they have same responsibilities but society does not accept it